INNOVATION DEVELOPMENT STRATEGY FOR KARANGPATIHAN CIPRAT BATIK AS AN EFFORT TO IMPROVE THE LOCAL ECONOMY - Afifah, Azizatul; Purnomo, Rochmat Aldy; Cahyono, Yeni (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
The batik industry is an industry that is relied upon in the local market as well as the export market in the textile sector. Likewise, Karangpatihan ciprat batik (splashed motif in batik) is deliberately empowered as a form of local government concern for disabled residents who have limitations. This research aims to analyze the strategy for developing Ponorogo's typical Karangpatihan ciprat batik in order to increase industrial competitiveness batik industry in Ponorogo Regency. The method used in this research is a qualitative approach using the SWOT analysis method and a survey conducted on the Karangpatihan village head and the chairman of Rumah Harapan Mulya as the Karangpatihan Social Welfare Institution. The results of the research analysis conclude that the strategies that can be used are determining market opportunities based on geographic location, demographics and consumer behavior, identifying the target market to be addressed both within and outside the city of Ponorogo by understanding consumer preferences and needs regarding batik, increasing human resource development in order to achieve this. more innovative quality batik products that can increase consumer appeal. Determining sales channels by considering the place and method to be used. Then determine competitive prices by adjusting product quality and competition in the market, protection of rights to regional typical batik products with Intellectual Property Rights, promotional program innovations aimed at introducing batik on the national and international stage to encourage sales and establishing good relationships with consumers and distributors so that it can expand the marketing of batik products.